2008
DOI: 10.1177/0192623308327409
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Differences in Sensitivity to Alterations of Mandible Structure Caused by the Teratogen 2,3,7,8-Tetrachlorodibenzo-p-Dioxin

Abstract: The contaminant 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) is an environmental pollutant and teratogen that has been shown to alter craniofacial development. Differences in sensitivity to TCDD are attributed primarily to differences in alleles at the Ahr locus coding for the aryl-hydrocarbon receptor (AHR) that binds TCDD and mediates its effects by altering gene expression. The authors used geometric morphometric methods to evaluate differences in the effects of small in utero exposures of TCDD on adult mandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Additional studies performed in zebrafish reported that TCDD-induced craniofacial defects are mediated by AHR signaling. However, the defects are uniquely found in the lower jaw, affecting the structure of the mandible and the development of the Meckel's cartilage (Keller et al, 2008;Planchart and Mattingly, 2010), highlighting possible evolutionary divergences between zebrafish and mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies performed in zebrafish reported that TCDD-induced craniofacial defects are mediated by AHR signaling. However, the defects are uniquely found in the lower jaw, affecting the structure of the mandible and the development of the Meckel's cartilage (Keller et al, 2008;Planchart and Mattingly, 2010), highlighting possible evolutionary divergences between zebrafish and mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypes and alleles of developmental genes can be influenced by genetic background [ 104 , 105 ]. An interesting and highly relevant example is the fact that different inbred strains of mice display differential response to AhR-mediated effects on mandible development [ 106 ]. The morphs studied here all (except AC) exist in sympatry in Lake Thingvallavatn.…”
Section: Discussionmentioning
confidence: 99%
“…If L–E rats have a longer and/or later period of facial growth by comparison, during adulthood their faces may remain more susceptible to environmental stressors [53] , [54] , [55] , which can alter natural between-strain differences in cranial shape [56] . Furthermore, although the H/W and L–E rats have different AhR alleles, five inbred strains of mice that possess the same AhR alleles have shown different TCDD-induced changes in mandibular size and shape [15] . These findings suggest that between-strain differences in TCDD responses may involve genes beyond the AhR locus, such as those that control the genetic architecture of a particular trait [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although the H/W and L–E rats have different AhR alleles, five inbred strains of mice that possess the same AhR alleles have shown different TCDD-induced changes in mandibular size and shape [15] . These findings suggest that between-strain differences in TCDD responses may involve genes beyond the AhR locus, such as those that control the genetic architecture of a particular trait [15] . Consistent with these findings, our results suggest that genetically programmed differences in growth potential may modulate TCDD toxicity in different rat stains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation